Nature of non-B, non-T lymphomas: an immunohistological study on frozen tissues using monoclonal antibodies. - Pallesen, G; Beverley, P; Lane, E; Madsen, M; Mason, D; Stein, H (BMJ Publishing Group, 1984)
In a previous study employing conventional immunological marker analysis we found that 17% of high grade malignant lymphomas were devoid of cytoplasmic and membrane immunoglobulin and also sheep erythrocyte receptors. Cryostat sections from 24 of these cases (four of low grade and 20 of high grade malignancy) were stained with a panel of 30 monoclonal antibodies and six polyclonal antisera using a sensitive immunoperoxidase method. All tumours expressed the leucocyte common antigen (detected by monoclonal antibody 2D1) and all lacked epithelial cytokeratin (monoclonal antibody LE61), confirming their haematopoietic origin. All but one of the lymphomas expressed antigens characteristic of either B cells (17 cases) or T cells (six cases), while one case (morphologically a centroblastic lymphoma) had an unusual dual phenotype in which strong staining for T6 (marker of immature T cells) was associated with expression of the pan B lymphocyte antigens detectable with To15, anti-B1, anti-Leu12. This case was therefore classified as a B cell lymphoma showing aberrant expression of the T6 antigen. The pan B cell antibodies (To15, anti-B1, anti-Leu12) all appeared highly specific and sensitive, but the simultaneous use of all three monoclonal antibodies was necessary to detect the B cell nature in each of the 18 lymphomas. A wider panel of monoclonal antibodies was required to detect T lymphomas since these often disclosed atypical and restricted phenotypes. To15 and UCHT1 were the most reliable antibodies for the detection of B and T cell neoplasms, respectively. We conclude that most, if not all, "non-B, non-T" lymphomas are of either B or T lymphocyte origin and that monoclonal antibodies provide indispensable tools in their classification and diagnosis.